The impact of transfer pricing regulations on profit shifting within European multinationals - Theresa Lohse; Nadine Riedel (Universität Hohenheim, Forschungszentrum Innovation und Dienstleistung (FZID), 2012)
Over the past decade, several countries augmented their national tax law by transfer pricing legislations in order to limit opportunities for tax-motivated transfer price distortions and the associated relocation of multnational income from their borders. The aim of this paper is to empirically investigate the impact of transfer pricing laws on multinational profit shifting behaviour. To do so, we collect unique data on the evolution of national transfer price requirements in Europe over the past decade. This data is linked to accounting information on multinational firms in the EU and to corporate tax rate data. In line with previous studies, we find that multinational firms engage in significant tax-motivated profit shifting behaviour. The analysis furthermore suggests that transfer price documentation rules are instrumental in restricting income shifting activities. The effect is statistically significant and economically relevant. Our analysis thus underpins the benefits of implementing transfer price documentation requirements and suggests that they may be socially desirable despite the high administrative burden they impose on firms and tax authorities.
urn:nbn:de:bsz:100-opus-7962
Keywords: F23; H25; 330; corporate taxation; international profit shifting; transfer price documentation requirements